2013
DOI: 10.1002/aenm.201300160
|View full text |Cite
|
Sign up to set email alerts
|

A High Capacity Calcium Primary Cell Based on the Ca–S System

Abstract: Conversion reaction cells afford the ability to explore new energy storage paradigms that transcend the dogma of small, low‐charge cations essential to intercalative processes. Here we report the use of earth‐abundant and green calcium and sulfur in unprecedented conversion reaction Ca–S primary cells. Using S‐infiltrated mesoporous carbon (abbreviated S@meso‐C) cathodes, we achieve discharge capacities as high as 600 mAh g−1 (S basis) within the geometry Ca|Ca(ClO4)2/CH3CN|S@meso‐C, at a discharge rate of C/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
118
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 32 publications
6
118
1
1
Order By: Relevance
“…This indicates that Li as well as Ca deposition on Ca in TFA‐TEGDME is unlikely. The initial plateau for discharge occurs at 1.5 V versus Ca, which is in agreement with the previous observation that Ca dissolution in most of the organic solvents requires an SEI breakdown potential of approximately 1 V . We also observed a similar degrading trend in CaLi 2 –sulfur cells using elemental sulfur, Super P, and LiTFA‐TEGDME; the passivation of polysulfides on a CaLi 2 anode quickly quenched the cells after the first cycle (Figure S5 in the Supporting Information) …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that Li as well as Ca deposition on Ca in TFA‐TEGDME is unlikely. The initial plateau for discharge occurs at 1.5 V versus Ca, which is in agreement with the previous observation that Ca dissolution in most of the organic solvents requires an SEI breakdown potential of approximately 1 V . We also observed a similar degrading trend in CaLi 2 –sulfur cells using elemental sulfur, Super P, and LiTFA‐TEGDME; the passivation of polysulfides on a CaLi 2 anode quickly quenched the cells after the first cycle (Figure S5 in the Supporting Information) …”
Section: Resultssupporting
confidence: 90%
“…[1,24] We also observed as imilard egrading trend in CaLi 2 -sulfur cells using elemental sulfur,S uper P, and LiTFA-TEGDME;t he passivation of polysulfides on aC aLi 2 anode quicklyq uenched the cells after the first cycle ( Figure S5 in the Supporting Information). [24] CaLi 2 greatly affects the morphologye volution of the dischargep roducts.T ypical Li 2 O 2 flat toroidsw ith surface crystalline nanoparticlesw ere observed in Li-O 2 cells when using LiTFA-TEGDME (Figure 3a-c). [25] Using the CaLi 2 anode leads to the formation of spherical (2-4 mm) and layered microparticles ( % 10 mm) in LiTFA-and Ca(TFA) 2 -TEGDME,r espectively,a tt he full discharge condition (Figure 3d-i and Figure S6 in the Sup- ChemSusChem 2020, 13,574 -581 www.chemsuschem.org porting Information).…”
Section: Super Pmentioning
confidence: 54%
“…However, to date, there has been only one study on calcium-sulfur (Ca-S) batteries, and the Ca-S cells demonstrated in that study were not reversible. [15] Furthermore, the Ca-S cell showed a low discharge voltage due to lack of an effective electrolyte.Herein, we present, for the first time, a reversible Ca-S battery enabled by a lithium-ion mediation strategy. The Ca-S battery is developed with a hybrid electrolyte comprised of a mixture of lithium and calcium ions.…”
mentioning
confidence: 99%
“…However, to date, there has been only one study on calcium-sulfur (Ca-S) batteries, and the Ca-S cells demonstrated in that study were not reversible. [15] Furthermore, the Ca-S cell showed a low discharge voltage due to lack of an effective electrolyte.…”
mentioning
confidence: 99%
“…Previous work on calcium primary batteries include the Ca-S system, 16 the Ca/Ca(AlCl 4 ) 2 /SOCl 2 system, [17][18][19][20] as well as thermal cells using lithium-based molten salts; 21,22 reversible behavior has not yet been demonstrated in these systems except for the molten salt batteries when heated above 400…”
mentioning
confidence: 99%